نموذج خط القرآن على أساس التعلم التعاوني على تطوير LPTQ فى سومطرا الغربية - Moh In’ami; Edi Setiawan; Etika Vestia; Ahmad Falah (Universitas Negeri Malang, 2022)
This study aimed: a realistic description of learning the khat Qur'an conducted by LPTQ in each development activity; develop the design of an educational model based on collaborative learning based on the khat Qur'an on the development of LPTQ; and test the validity, process and effectiveness of developing an educational model based on collaborative learning based on the khat Qur'an on LPTQ.The methodology used in this study is the R&D method developed by Thiagarajan, which includes four steps better known as D4, namely definition, design, development and publishing. Typical trials were conducted on LPTQ training and training activities. The results of the study found an actual model for learning the traditional khat Qur'an organized by LPTQ. The form contains: 1) delivery of objectives and motives, 2) physical and important explanations, 3) participants create work independently, 4) guidance at work, 5) presentation of work, 6) evaluation and correction. Find a model to learn the khat Qur'an based on collaborative learning. Learning activities are supported by a standard educational guide to the khat Qur'an.